1988
DOI: 10.1530/jrf.0.0830687
|View full text |Cite
|
Sign up to set email alerts
|

Immunologically reactive albumin-like protein in human testis and seminal plasma

Abstract: An immunologically reactive albumin-like protein (albumin) was localized, by an immunostaining technique, in the testis of infertile men (normal spermatogenesis, obstructive azoospermia) at the level of the Sertoli cells and in some cells of the germinal epithelium (secondary spermatocytes and early spermatids). No positive reaction was detectable in prepubertal testis. In vasectomized men, mean seminal albumin values were drastically reduced (by about 80%) in comparison to fertile controls, indicating a proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…These results suggest that during HSA-PIP complex formation, the secondary structure of HSA is partially disordered. Human seminal plasma is a rich source of HSA and it may originate from prostate [21], epididymis or testis [22]. Orlando et al (1988) correlated its presence in seminal fluid to its ability to transport androgens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that during HSA-PIP complex formation, the secondary structure of HSA is partially disordered. Human seminal plasma is a rich source of HSA and it may originate from prostate [21], epididymis or testis [22]. Orlando et al (1988) correlated its presence in seminal fluid to its ability to transport androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Human seminal plasma is a rich source of HSA and it may originate from prostate [21], epididymis or testis [22]. Orlando et al (1988) correlated its presence in seminal fluid to its ability to transport androgens. HSA can bind cholesterol efficiently and current understanding points towards a model in which cholesterol diffuses out of sperm spontaneously and presence of an acceptor in the medium results in net loss of this lipid from sperm membrane resulting in altered lipid composition favoring capacitation [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other proteins are produced by the Sertoli cells and can be divided into testis‐specific (inhibin) and serum‐like (e.g. transferrin, somatomedin‐C, ceruloplasmin and plasminogen activator) proteins (Orlando et al. 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The authors studied the following proteins: a 82-kDa protein identified as lactoferrin which derives from seminal vesicles (Hekman & Rumke 1968;Lilja et al, 1987;Autiero et al, 1991); a 50kDa protein and a 34-kDa protein identified respectively as the two reduced subunities of prostatic-acid phosphatase and prostate-specific antigen which are the two main prostatic products (Rui et al, 1984;Balerna et al, 1990;Autiero et al, 1991); and a 66 kDa protein identified as albumin which derives in seminal plasma from different sources such as prostate, seminal vesicles and testis (Rui et al, 1984;Orlando et al, 1988;Balerna et al, 1990;Autiero et al, 1991). Part of it is transferred also through circulation to the lower genital tract (Chard et al, 1991).…”
Section: Seminal-plasma Proteins Investkatedmentioning
confidence: 99%